Tradisi Tahlilan dalam Perspektif Nahdlatul Ulama dan Muhammadiyah: Studi Komparatif - Saif Ali Bavana; Mausol Akmal Asyuro; Abdillah Tsany; Muhamad Mas’ud; Siti Munawati (Tadabbur: Jurnal Integrasi Keilmuan, 2025)
This study aims to analyze and compare the perspectives of Nahdlatul Ulama (NU) and Muhammadiyah on the tahlilan tradition, which is widely practiced among Indonesian Muslims. The research employs a qualitative approach using the library research method by examining relevant books, scholarly journals, and other academic literature related to the topic. The findings reveal that Nahdlatul Ulama accepts tahlilan as a religious tradition that incorporates elements of dhikr, prayer, and social values that strengthen solidarity and communal cohesion. In contrast, Muhammadiyah does not regard tahlilan as a specifically prescribed Islamic practice, as it emphasizes adherence to the Qur’an and the Sunnah as the primary foundations of worship. Despite these differing perspectives, both organizations acknowledge the importance of offering prayers for the deceased. The study further indicates that these differences primarily stem from their distinct methodological approaches to interpreting and applying the sources of Islamic teachings, which ultimately shape their respective religious perspectives and practices within the Indonesian Muslim community.